1991
DOI: 10.1080/01904169109364262
|View full text |Cite
|
Sign up to set email alerts
|

Ferric reduction bygeum urbanum: A kinetic study

Abstract: The reduction capacity for ferric chelates of Geum urbanum L. showed a marked increase when plants were grown under conditions of ironshortage. Ferric ethylenediaminetetraacetate (FeEDTA) was reduced with a pH optimum between 5 and 6. The reaction exhibited a low substrate affinity with a K m much higher than the expected concentration range of soluble iron in the soil. Analysis of the saturation plots conform to Michaelis-Menten kinetics. Both V max and K m values varied to a broad extent with changing assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…The apparent K , values we obtained were about 1 order of magnitude higher than those obtained by previous Bienfait et al [1983]), Lycopevsicon esculenfum (230 p~; Brüggemann et al [1990]), and Geuin uvbanum (87 p~; Schmidt and Janiesch [1991]). Our results were most similar to those of Susín et al (1996), who reported a K , of 514 PM in Fe-deficient Beta vulgaris.…”
Section: O Cu Deficiency and Fe Deficiency Lnduce The Same Ferric Rcontrasting
confidence: 52%
“…The apparent K , values we obtained were about 1 order of magnitude higher than those obtained by previous Bienfait et al [1983]), Lycopevsicon esculenfum (230 p~; Brüggemann et al [1990]), and Geuin uvbanum (87 p~; Schmidt and Janiesch [1991]). Our results were most similar to those of Susín et al (1996), who reported a K , of 514 PM in Fe-deficient Beta vulgaris.…”
Section: O Cu Deficiency and Fe Deficiency Lnduce The Same Ferric Rcontrasting
confidence: 52%
“…Decreases in the activity of the FC-R in Fe-deficient plants at high pH have been reported before for intact plants of peanut (Romheld and Marschner, 1983), apple (Ao et al, 1985), Ficus benjamina (Rosenfield et al, 1991), G. urbanum (Schmidt and Janiesch, 1991a), and A. thaliana (Moog et al, 1995). However, in most of these cases the pH www.plantphysiol.org on March 24, 2019 -Published by Downloaded from Copyright © 1996 American Society of Plant Biologists.…”
Section: Discussionmentioning
confidence: 82%
“…Data previously presented by Schmidt and Janiesch (1991a) indicated that the maximal rate of reduction by G.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations